Identification of Fruit Traits Related QTLs and a Candidate Gene, CaBRX, Controlling Locule Number in Pepper (Capsicum annuum L.) - Xiao Ma; Yi-Ming Qiao; Yang Li; Ya-Nan Yu; Zhen-Hui Gong (Horticulturae, 2022)
Fruit traits are important in pepper (Capsicum annuum L.) and affect its quality and yield. These traits are controlled by quantitative trait loci (QTLs). In this study, we identified many major QTLs that control fruit length (Ftl), fruit diameter (Ftd), fruit shape (Fts), fruit weight (Ftw) and locule number (Lcn) in the F2 and F2:3 populations developed from the QTL mapping of GS6 (P1) and Qiemen (P2). A total of 111 simple sequence repeats and insertion/deletion markers were utilized to construct a linkage map with 12 linkage groups over a length of 1320.72 cM. An inclusive composite interval mapping analysis indicated that many QTLs were detected and included ftl2.1, ftd2.1, fts1.1, ftw2.1 and lcn1.1. As a novel QTL, lcn1.1 was located between HM1112 and EPMS709, and the genetic distance was 3.18 cM covering 60 predicted genes. Within the region, we identified Capana01g004285 as a candidate gene by functional annotation and expression analysis and found that it encodes the BREVIS RADIX (BRX) protein. Knockdown of CaBRX through the virus-induced gene silencing approach in GS6 reduced the number of locules and influenced the expressions of genes related to flower and locule development, suggesting that CaBRX plays an important function in the development of locules.